Analysis of a self-supporting bamboo structure with flexible joints. Issue 2 (June 2021) - Seixas, Mario; Moreira, Luís Eustáquio; Stoffel, Patrick; Bina, João; Ripper, José Luiz Mendes; Ferreira, Jorge Lucas; Ghavami, Khosrow
Self-supporting bamboo structures are ultralight architectural modules applying bamboo round poles, tensile pantographic grids and textile membranes. The structural system applies articulated flexible joints in polyester ropes and locking bio-composite bandage rings, keeping bamboo bars free of torsion stresses. An experimental 1:3 scale prototype and a full-scale structure were fabricated to make previsions about the physical and mechanical behavior of the structure. The experimental results were verified applying a numerical model for the structure. In turn, the flexible joints were analyzed theoretically. The computer model was analyzed using the finite element SAP2000 program. The numerical results were in close agreement with the experimental results specifically for the structural behavior of the flexible joints.